Effect of Ruta graveolens (Rue) essential oil in high concentrations on Staphylococcus aureus subsp aureus strain ATCC® 25904 - Montero Recalde, Mayra Andrea (2025)
The objective of the research was to evaluate the antimicrobial efficacy of the essential oil of ruda (Ruta graveolens) onStaphylococcus aureus subp aureus strain ATCC ®25904. the plant was collected from the Inapisí sector of Constantino Fernández, the oil was obtained with the hydrodistillation technician, 10 concentrations were evaluated (10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100% ) in dilution with double distilled water, each dilution was handled a total of 5 ml and tween 80 was added as 0,1% as emulsifier, the results showed that the determined minimum inhibitory concentration of the essential oil was defined at 30%; with respect to the Bactericidal minimum concentration evidenced by the zero growth of colonies on the plate, which was established at 40% concentration; the antimicrobial sensitivity study statistically show significant differences between treatments with the 0,5% Tukey test, the best being at 90% concentration with 25,25 mm of inhibition halo formation, however the treatments starting at 30% and showed significant halos formation, concluding that Ruta graveolens oil has antimicrobial efficacy on the strain evaluate.